Cultural values and self-directed learning among female Malay adult learners / Badli Esham Ahmad - Esham Ahmad, Badli (2016)
Research into Malay adult learners and self-directed learning in Malaysia is far from its saturation point and still offers many avenues for research. There appeared to be a gap in research information on the Malay cultural values and self-directed learning. Limited research has been conducted to close the gap between Malay cultural values and self-directed learning. Hence, the study undertook the task of closing the gap between Malay cultural values and self-directed learning by looking at how the Malay cultural values help to shape the self-directedness of the Malay adult learners. The research employed the qualitative approach and used journal entries, observations and interviews as its data collection method. Six Malay cultural values derived from literature were chosen- harmonious, collective, sensitive, approval seeking, religious and maintaining face as the cultural values upheld by the Malays. Four Malay adult learners who were pursuing postgraduate degrees in a local university participated in the study. The study found that three participants were very self-directed while the other participant was less self-directed. The findings also indicated four pertinent Malay cultural values in the participants-harmonious, collective, sensitive and maintaining face and these Malay cultural values helped to shape the Malay adult learners. It was found that these Malay cultural values help shaped the respondents to become a careful adult learner, a survivor, an active learner and an optimistic learner. Hence, the study would conclude that cultural values have a role to play in shaping the self-directedness of the Malay adult learners. As such, the study recommends a cultural process framework and an inventory to better understand how cultural values help to shape the self-directed learning of the Malay adult learners.